Urgency and clinical-surgical dental emergency in primary care - elaboration and validation of an e-book (Research, Society and Development, 2023)
Objective: To develop and validate an e-book on clinical-surgical dental urgency and emergency in primary care. Methods: For content validation, 23 judges participated. The judges received the e-book via e-mail along with the access link to the content validation questionnaire through a digital form (Google Forms®), with questions regarding the e-book content, regarding the objective, structure, presentation and relevance. Results and discussion: The scores achieved in the approval rate of 95.3%, in the structure and presentation criteria the questions reached the approval rate of 90.8% and in the relevance criterion, it reached an index of 95.3%. The evaluated criteria did not show a statistically significant difference in either the Cronbach's alpha coefficient or the Content Validity Index (CVI). Conclusion: In general, including all the criteria evaluated, the product obtained a general acceptance rate of 93% of approval of the content, presenting conditions to circulate in the clinical-surgical environment as a support tool for professionals in primary care dentistry.